Practical Implications of Empirically Studying Moral Decision-Making - Heinzelmann, Nora; Ugazio, Giuseppe; Tobler, Philippe (Frontiers in Neuroscience, 2012)
This paper considers the practical question of why people do not behave in the way they ought to behave. This question is a practical one, reaching both into the normative and descriptive domains of morality. That is, it concerns moral norms as well as empirical facts. We argue that two main problems usually keep us form acting and judging in a morally decent way: firstly, we make mistakes in moral reasoning. Secondly, even when we know how to act and judge, we still fail to meet the requirements due to personal weaknesses. This discussion naturally leads us to another question: can we narrow the gap between what people are morally required to do and what they actually do? We discuss findings from neuroscience, economics, and psychology, considering how we might bring our moral behavior better in line with moral theory. Potentially fruitful means include nudging, training, pharmacological enhancement, and brain stimulation. We conclude by raising the question of whether such methods could and should be implemented.